Application of the Preclinical Alzheimer's Cognitive Composite for tracking progression in cognitively unimpaired older adults with known Amyloid status: A 24‐month Interim Analysis of the Chariot‐Pro cohort. (20th December 2022) - Novak, Gerald P; Udeh‐Momoh, Chinedu T.; Price, Geraint J; Baker, Susan; de Jager, Celeste A; Giannakopoulou, Parthenia; Middleton, Lefkos T
Abstract: Background: The ongoing CHARIOT‐PRO Substudy aims to estimate the rate of cognitive change in the early Alzheimer's pathological continuum, comparing individuals with and without baseline biomarker evidence of amyloid deposition, over a 4.5yr follow up. We previously reported subtle cognitive differences between the two groups at baseline. Here we extend follow‐up to 24m. Method: Cognitively unimpaired individuals aged 60–85 years, in good general health and with global Clinical Dementia Rating (CDR) scale = 0, underwent amyloid assessment via PET or lumbar puncture; approximately equal numbers of amyloid positive (A+) and amyloid negative (A‐) individuals were enrolled. This report focuses on the preclinical Alzheimer's cognitive composite (PACC) total score and the CDR, performed at baseline and at M12 and M24. Subtle deficit at baseline was defined as PACC scores below the 15 th percentile of A‐ individuals. The A+ and A‐ groups were compared on rate of progression to CDR > 0 and annualized change from baseline in PACC. Individuals with and without progression at any point in the CDR were compared with respect to PACC baseline and change scores. Result: A+ participants had lower PACC scores at baseline (‐0.39 (2.56) vs 0.40 (2.71), p = 0.001). There was a trend for less improvement at M24 (0.29 (2.1) vs 0.62 (1.76), p = 0.068). More A+ than A‐ participants progressed to CDR = 0.5 (Figure 1; Kaplan‐Meier survival 84.6% vs 93.1%, respectively, p = 0.004). Those with subtle deficit at baseline were more likely to progress to CDR = 0.5 (14.1% vs 5.9%, OR = 2.63, p = 0.008). Participants with progression to CDR = 0.5 at any time had lower PACC scores at baseline (‐1.30 (2.72) vs 0.24 (2.59), p < 0.0005) and greater decline at M24 (‐0.30 (2.20) vs 0.55 (1.88), p = 0.014). Conclusion: In A+ individuals, a greater decline in mean PACC scores trended towards significance at 24m, a larger proportion had change in CDR, and CDR progression was associated with declining PACC. In addition, low baseline PACC predicted subsequent increase from CDR = 0. These findings provide further evidence that the PACC has sufficient sensitivity to measure subtle cognitive deficits and serve as an indicator of progression on the early Alzheimer's pathological continuum.